Low-magnetic concrete, and preparation method and application thereof

CN122916540APending Publication Date: 2026-10-16HUNAN CSCEC5B CONCRETE +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611078361.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

这种方式存在明显的局限性:工业级原料中不可避免地残留有ppm级的微量铁杂质,在常规水泥水化进程中,这些游离的铁离子仍会富集并结晶转化为具有自发磁矩的铁磁性或亚铁磁性微区(如磁铁矿、针铁矿等),导致硬化基体产生本底剩磁,难以将相对磁导率压低至极限水平

Benefits of technology

本发明引入的微量1-羟基乙烷-1,1-二膦酸(HEDP)利用其多齿配体结构,在强碱性孔隙液中对微量Fe3+展现出极高的螯合稳定常数。HEDP 抢先与游离的Fe3+发生多中心配位,将铁离子孤立并包裹在高度分散的非晶态有机膦酸铁螯合物中。由于各个铁离子的自旋磁矩被有机大分子网格磁隔离,无法形成长程磁有序结构,从而由“铁磁性”转变为完全无自发磁矩的“顺磁性”,从源头上消除了混凝土的微观剩磁与磁畸变。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses low-magnetic concrete and a preparation method and application thereof; the concrete comprises the following components in parts by weight: white silicate cement 360-420 parts; metakaolin 40-70 parts; coarse aggregate 950-1050 parts; fine aggregate 650-730 parts; early strength activator 1.0-3.5 parts; 1-hydroxyethane-1,1-diphosphonic acid 0.05-0.25 parts; and polycarboxylic acid water reducing agent 1-10 parts. The trace 1-hydroxyethane-1,1-diphosphonic acid (HEDP) and the early strength activator introduced in the application can realize good mechanical properties and good low magnetism.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of concrete technology, and in particular to a low-magnetic concrete, its preparation method, and its application. Background Technology

[0002] With the development of modern science and technology, the requirements for the stability of the magnetic field around experimental environments and engineering facilities are constantly increasing in fields such as weak magnetic field detection, precision measurement, underground scientific experiments, space science research, and high-sensitivity magnetic field detection. Concrete, as one of the most widely used building materials in engineering construction, typically contains iron oxides, iron-containing minerals, and other impurities with magnetic response characteristics. Under the influence of the Earth's magnetic field or external magnetic fields, it may undergo magnetization, thus affecting the surrounding magnetic field. Therefore, developing concrete materials with low or even ultra-low magnetic properties is of great significance for reducing the magnetic interference of building structures themselves, ensuring a precise experimental environment, and promoting the construction of related special engineering facilities.

[0003] However, existing low-magnetic concrete mainly relies on the physical screening of raw materials, namely, reducing the total iron content by using bulk raw materials such as low-iron white silicate cement and high-purity quartz sand. This approach has significant limitations: industrial-grade raw materials inevitably contain trace amounts of iron impurities at the ppm level. During the conventional cement hydration process, these free iron ions will still accumulate and crystallize, transforming into ferromagnetic or ferrimagnetic microregions with spontaneous magnetic moments (such as magnetite and goethite), resulting in background remanence in the hardened matrix, making it difficult to reduce the relative permeability to the limit level. In addition, conventional low-magnetic concrete often exhibits high brittleness and easy cracking defects due to its low iron content. If traditional steel fibers are incorporated to resist cracking, the low magnetic properties will be directly destroyed. If ordinary polymer fibers or non-metallic fibers are introduced, on the one hand, exogenous magnetic particles are easily introduced in the fiber drawing and manufacturing chain, and on the other hand, the fibers are very easy to agglomerate and disperse unevenly in the cement matrix. Furthermore, the interfacial transition zone (ITZ) between the fibers and the matrix is ​​prone to peeling and damage, resulting in a serious conflict between the overall mechanical toughness of the component and the three-dimensional uniformity of the magnetic field.

[0004] In view of this, there is an urgent need to develop a fiber-free, self-reinforcing, ultra-low magnetic high-strength concrete. Summary of the Invention

[0005] The present invention aims to at least solve one of the technical problems existing in the prior art. To this end, the first aspect of the present invention proposes a low-magnetic concrete that not only has low magnetic properties but also high mechanical properties.

[0006] A second aspect of the present invention also provides a method for preparing low-magnetic concrete.

[0007] A third aspect of the present invention also provides an application of low-magnetic concrete.

[0008] According to a first aspect of the present invention, a low-magnetic concrete comprises the following components in parts by weight: 360-420 parts of white silicate cement; 40-70 parts of metakaolin; 950-1050 parts of coarse aggregate; 650-730 parts of fine aggregate; 1.0-3.5 parts of early strength activator; 0.05-0.25 parts of 1-hydroxyethane-1,1-diphosphonic acid; 1-10 parts of polycarboxylate superplasticizer.

[0009] According to a preferred embodiment of the present invention, the weight ratio of the early-strength activator to the 1-hydroxyethane-1,1-diphosphonic acid is (10~40):1.

[0010] According to a preferred embodiment of the present invention, the weight ratio of the early-strength activator to the 1-hydroxyethane-1,1-diphosphonic acid is (20~30):1.

[0011] According to a preferred embodiment of the present invention, the early strength activator includes anhydrous sodium sulfate and / or triethanolamine.

[0012] According to a preferred embodiment of the present invention, the white silicate cement has a strength grade greater than or equal to PW 52.5, and the mass fraction of Fe2O3 in the cement is less than 0.15%.

[0013] According to a preferred embodiment of the present invention, the coarse aggregate has a particle size of 5-20 mm and is continuously graded.

[0014] According to a preferred embodiment of the present invention, the fine aggregate includes at least one of quartz sand, natural sand, and manufactured sand.

[0015] According to a preferred embodiment of the present invention, the D50 particle size of the metakaolin is 1~10μm.

[0016] The low-magnetic concrete according to embodiments of the present invention has at least the following beneficial effects: The present invention introduces trace amounts of 1-hydroxyethane-1,1-diphosphonic acid (HEDP), which utilizes its multidentate ligand structure to react with trace amounts of Fe in strongly alkaline pore liquids. 3+ It exhibits an extremely high chelation stability constant. HEDP preemptively binds to free Fe. 3+ Multicenter coordination occurs, isolating and encapsulating iron ions within highly dispersed amorphous organophosphonate iron chelates. Because the spin magnetic moments of each iron ion are magnetically isolated by the organic macromolecular network, they cannot form a long-range magnetically ordered structure, thus transforming from "ferromagnetism" to "paramagnetism" with no spontaneous magnetic moment, eliminating microscopic remanence and magnetic distortion in concrete at its source. Furthermore, this invention introduces an early-strength activator through compounding. The anions or alkali metal ions released by the activator occupy active sites on the surface of cement particles through competitive adsorption, thereby displacing some of the adsorbed HEDP. On the other hand, the activator strongly stimulates and accelerates the dissolution and reaction of tricalcium aluminate in the early stages of hydration, forcibly consuming calcium ions in the pore fluid to accelerate the explosive crystallization of early hydration products (such as ettringite nuclei). This solves the problem of the impact of HEDP on the hydration process.

[0017] Furthermore, the ultrafine active metakaolin deliberately introduced in this invention triggers a strong pozzolanic reaction in the later stages of hydration, absorbing the Ca(OH)2 crystals produced during hydration and transforming them into high-density CSH gel. Simultaneously, due to the microscopic control of crystal growth orientation by HEDP, some hydration products tend to grow densely into the interior of the micropores, ultimately constructing a macroscopically homogeneous high-performance concrete with high impermeability and high flexural strength in a fiber-free state.

[0018] According to a second aspect of the present invention, a method for preparing low-magnetic concrete as described in the first aspect of the present invention is provided, comprising the following steps: S1. Add white silicate cement, metakaolin, coarse aggregate and fine aggregate to a mixer to obtain dry material; dissolve 1-hydroxyethane-1,1-diphosphonic acid, early strength activator and polycarboxylate superplasticizer in water to prepare a mixture; S2. The mixture and the dry material are mixed and stirred to obtain the final product.

[0019] A third aspect of the present invention provides the application of low-magnetic concrete as described in the first aspect of the present invention in the construction of precision micromagnetic environment engineering.

[0020] According to a preferred embodiment of the present invention, the precision micro-magnetic environment engineering includes a medical MRI room, a quantum computing laboratory, an ultra-high resolution electron microscope center, or a maglev rail transit project; the concrete is used to pour the magnetic shielding walls, structural load-bearing beams, or precision equipment foundation bases in the above-mentioned projects.

[0021] Other features and advantages of the invention will be set forth in the description which follows, and will be apparent in part from the description, or may be learned by practicing the invention. Detailed Implementation

[0022] The following are specific embodiments of the present invention, and the technical solutions of the present invention will be further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.

[0023] Unless otherwise specified, the reagents, methods and equipment used in this invention are all conventional reagents, methods and equipment in this technical field.

[0024] In some embodiments of the present invention, a low-magnetic concrete is provided, comprising the following components in parts by weight: 360-420 parts of white silicate cement; 40-70 parts of metakaolin; 950-1050 parts of coarse aggregate; 650-730 parts of fine aggregate; 1.0-3.5 parts of early strength activator; 0.05-0.25 parts of 1-hydroxyethane-1,1-diphosphonic acid; 1-10 parts of polycarboxylate superplasticizer.

[0025] It is understood that the trace amounts of 1-hydroxyethane-1,1-diphosphonic acid (HEDP) introduced in this invention utilize its multidentate ligand structure to react with trace amounts of Fe in strongly alkaline pore liquids. 3+ It exhibits an extremely high chelation stability constant. HEDP preemptively binds to free Fe. 3 + Multicenter coordination occurs, isolating and encapsulating iron ions within highly dispersed amorphous organophosphonate iron chelates. Because the spin magnetic moments of each iron ion are magnetically isolated by the organic macromolecular network, they cannot form a long-range magnetically ordered structure, thus transforming from "ferromagnetism" to "paramagnetism" with no spontaneous magnetic moment, eliminating microscopic remanence and magnetic distortion in concrete at its source. Furthermore, this invention introduces an early-strength activator through compounding. The anions or alkali metal ions released by the activator occupy active sites on the surface of cement particles through competitive adsorption, thereby displacing some of the adsorbed HEDP. On the other hand, the activator strongly stimulates and accelerates the dissolution and reaction of tricalcium aluminate in the early stages of hydration, forcibly consuming calcium ions in the pore fluid to accelerate the explosive crystallization of early hydration products (such as ettringite nuclei). This solves the problem of the impact of HEDP on the hydration process.

[0026] Furthermore, the ultrafine active metakaolin deliberately introduced in this invention triggers a strong pozzolanic reaction in the later stages of hydration, absorbing the Ca(OH)2 crystals produced during hydration and transforming them into high-density CSH gel. Simultaneously, due to the microscopic control of crystal growth orientation by HEDP, some hydration products tend to grow densely into the interior of the micropores, ultimately constructing a macroscopically homogeneous high-performance concrete with high impermeability and high flexural strength in a fiber-free state.

[0027] In some embodiments of the present invention, the weight ratio of the early-strength activator to the 1-hydroxyethane-1,1-diphosphonic acid is (10~40):1. For example, it includes sub-ranges such as 10:1, 12:1, 15:1, 18:1, 20:1, 22:1, 25:1, 28:1, 30:1, 32:1, 35:1, 38:1, 40:1, or any two of the above values. Therefore, the concrete of the present invention exhibits good low magnetic properties and high mechanical properties.

[0028] In some embodiments of the present invention, the weight ratio of the early-strength activator to the 1-hydroxyethane-1,1-diphosphonic acid is (20~30):1. For example, it includes sub-ranges such as 20:1, 21:1, 22:1, 23:1, 24:1, 25:1, 26:1, 27:1, 28:1, 29:1, 30:1, or any two of the above values. Therefore, the concrete of the present invention exhibits good low magnetic properties and high mechanical properties.

[0029] In some embodiments of the present invention, the early strength activator includes anhydrous sodium sulfate and / or triethanolamine.

[0030] In some embodiments of the present invention, the white silicate cement has a strength grade greater than or equal to PW 52.5, and the mass fraction of Fe2O3 in the cement is less than 0.15%.

[0031] In some embodiments of the present invention, the coarse aggregate has a particle size of 5-20 mm and is continuously graded.

[0032] In some embodiments of the present invention, the fine aggregate includes at least one of quartz sand, natural sand, and manufactured sand.

[0033] In some embodiments of the present invention, the D50 particle size of the metakaolin is 1~10μm.

[0034] In some embodiments of the present invention, the coarse aggregate, the fine aggregate, and the metakaolin all need to undergo magnetic separation treatment first.

[0035] In some embodiments of the present invention, a method for preparing low-magnetic concrete as described in the first aspect of the present invention is provided, comprising the following steps: S1. Add white silicate cement, metakaolin, coarse aggregate and fine aggregate to a mixer to obtain dry material; dissolve 1-hydroxyethane-1,1-diphosphonic acid, early strength activator and polycarboxylate superplasticizer in water to prepare a mixture; S2. The mixture and the dry material are mixed and stirred to obtain the final product.

[0036] In some embodiments of the present invention, the present invention provides an application of low magnetic concrete as described in the first aspect of the present invention in the construction of precision micromagnetic environment engineering.

[0037] In some embodiments of the present invention, the precision micro-magnetic environment engineering includes a medical MRI room, a quantum computing laboratory, an ultra-high resolution electron microscope center, or a maglev rail transit project; the concrete is used to pour the magnetic shielding walls, structural load-bearing beams, or precision equipment foundation bases in the above-mentioned projects.

[0038] In some embodiments of the present invention, some of the raw materials are as follows: White silicate cement: AALBORG WHITE PW 52.5, Alboportland (Anqing) Co., Ltd.; Metakaolin: "Chao Brand High-Activity Metakaolin (Median Particle Size D50 is 1.8-2.5μm)" produced by Inner Mongolia Chao Brand New Material Co., Ltd. Fine aggregate: Quartz sand: Jiangsu Pacific Quartz Co., Ltd.; 1-Hydroxyethane-1,1-Diphosphonic acid (HEDP): Shandong Taihe Technology Co., Ltd.; Early-strength activator: Triethanolamine, Yinyan Chemical High-purity TEA-99.5%; Jiangsu Yinyan Chemical Co., Ltd. Polycarboxylate superplasticizer: Subote SBT-CCP; Jiangsu Subote New Material Co., Ltd. Coarse aggregate: High-purity white marble ore from Quyang, Hebei Province, is used to produce 5-20mm continuously graded crushed stone after mechanical crushing and strong magnetic separation to remove iron.

[0039] In this embodiment of the invention, the raw materials need to be demagnetized: a dry magnetic separator is used for screening, which involves steps such as magnetization, sorting and collection.

[0040] Example 1 This example provides a low-magnetic concrete. The dosage of each component is shown in Table 1, and the preparation method is as follows: S1. Add white silicate cement, metakaolin, coarse aggregate and fine aggregate to a mixer to obtain dry material; dissolve 1-hydroxyethane-1,1-diphosphonic acid, early strength activator and polycarboxylate superplasticizer in water to prepare a mixture; S2. Mix the liquid and dry materials together and stir.

[0041] Examples 2-3 This example provides a series of low-magnetic concretes, prepared as shown in Example 1, with the dosage of each component shown in Table 1.

[0042] Table 1

[0043] Examples 4-7 This example provides a low-magnetic concrete, the preparation method of which is shown in Example 1, and the dosage of each component is shown in Table 2.

[0044] Table 2

[0045] Comparative Example 1 This example provides a low-magnetic concrete, which is prepared in the same way and in the same amount as in Example 1. The difference is that no early strength activator is added.

[0046] Comparative Example 2 This example provides a low-magnetic concrete, which is prepared in the same way and in the same amount as in Example 1, except that 1-hydroxyethane-1,1-diphosphonic acid is not added.

[0047] Performance testing The concrete samples from the embodiments and comparative examples of this invention were tested according to the following standards: Mechanical properties: Tested according to national standard GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete". Compressive strength: Standard cubic test blocks of 150 mm * 150 mm * 150 mm were cast. Flexural strength: Standard prism test blocks of 150 mm * 150 mm * 600 mm were cast.

[0048] Curing and Testing: After demolding, all specimens were moved to a standard curing room (temperature 20±2℃, relative humidity 95%) for 28 days. The compressive strength and flexural strength after 28 days were then measured.

[0049] Magnetic testing: The magnetism of the concrete in the above embodiments and comparative examples was tested. The specific method is as follows: Connect the magnetometer to the probe and fix it to the edge of the workbench, so that the center point of the probe is fixed at the same height as the middle of the test piece or standard container, and adjust the verticality; draw a straight line on the workbench 5cm away from the outer surface of the probe as the measurement distance mark; turn on the power switch, preheat for 5 minutes, and zero the instrument; keep the specimen or container in the same direction and posture, and place it in the magnetization device for magnetization for 3 minutes; accurately place the specimen or container on the measurement mark and measure the magnetic field value in sequence. The magnetic test results are shown in Table 3.

[0050] Table 3

[0051] As can be seen from the data in Table 3, the trace amounts of 1-hydroxyethane-1,1-diphosphonic acid (HEDP) and early strength activator introduced in the embodiments of the present invention can achieve both good mechanical properties and good low magnetic properties. The present invention has been described in detail above with reference to the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention.

Claims

1. A low-magnetic concrete, characterized in that, Includes the following components, calculated in parts by weight: 360-420 parts white silicate cement; 40-70 parts metakaolin; 950-1050 parts coarse aggregate; 650-730 parts fine aggregate; Early-strength activator: 1.0~3.5 parts; 0.05~0.25 parts of 1-hydroxyethane-1,1-diphosphonic acid; 1~10 parts of polycarboxylate superplasticizer.

2. The low-magnetic concrete according to claim 1, characterized in that, The weight ratio of the early-strength activator to the 1-hydroxyethane-1,1-diphosphonic acid is (10~40):

1.

3. The low-magnetic concrete according to claim 1 or 2, characterized in that, The weight ratio of the early-strength activator to the 1-hydroxyethane-1,1-diphosphonic acid is (20~30):

1.

4. The low-magnetic concrete according to claim 1, characterized in that, The early strength activator includes anhydrous sodium sulfate and / or triethanolamine.

5. The low-magnetic concrete according to claim 1, characterized in that, The white silicate cement has a strength grade greater than or equal to PW 52.5, and the mass fraction of Fe2O3 in the cement is less than 0.15%.

6. The low-magnetic concrete according to claim 1, characterized in that, The coarse aggregate has a particle size of 5-20 mm and is continuously graded.

7. The low-magnetic concrete according to claim 1, characterized in that, The fine aggregate includes at least one of quartz sand, natural sand, and manufactured sand.

8. A method for preparing low-magnetic concrete as described in any one of claims 1 to 7, characterized in that, Includes the following steps: S1. Add white silicate cement, metakaolin, coarse aggregate and fine aggregate to a mixer to obtain dry material; dissolve 1-hydroxyethane-1,1-diphosphonic acid, early strength activator and polycarboxylate superplasticizer in water to prepare a mixture; S2. The mixture and the dry material are mixed and stirred to obtain the final product.

9. The application of low-magnetic concrete as described in any one of claims 1 to 7 in the construction of precision micromagnetic environment engineering.

10. The application according to claim 9, characterized in that, The precision micro-magnetic environment engineering includes medical MRI rooms, quantum computing laboratories, ultra-high resolution electron microscope centers, or maglev rail transit projects; the concrete is used to pour magnetic shielding walls, structural load-bearing beams, or precision equipment foundation bases in the above-mentioned projects.